Signboard Text Translator: A Guide to Tourist - Ilaiah Kavati; G Kiran Kumar; Sarika Kesagani; K Srinivasa Rao (Institute of Advanced Engineering and Science, 2017)
The travelers face troubles in understanding the signboards which are written in local language. The travelers can rely on smart phone for traveling purposes. Smart phones become most popular in recent years in terms of market value and the number of useful applications to the users. This work intends to build up a web application that can recognize the English content present on signboard pictures captured using a smart phone, translate the content from English to Telugu, and display the translated Telugu text back onto the screen of the phone. Experiments have been conducted on various signboard pictures and the outcomes demonstrate the viability of the proposed approach.